Developing halal edugastronomy tourism framework based on maqasid shariah among muslim local food providers in Malaysia: a conceptual paper - W.N. Che Mat Safiee; S.S. Saffinee; M.A. Jamaludin; K. Mohd Noor; M.M. Mohd Salleh; N.S. Mohd (Rynnye Lyan Resources, 2026)
Tier 3- Indexed by MyCite